STRATEGI MSDM DALAM PENINGKATAN PROFESIONALITAS GURU SMKN 1 PALOPO - Dewanti, Winda; Kusdarianto, Indra; Wahida, Altri (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study investigates the efficacy of existing strategies in enhancing the professionalism of teachers at SMKN 1 Palopo. Utilizing a quantitative approach, the research involved a sample of 50 teachers. The analysis employed multiple linear regression to test hypotheses concerning the impact of three independent variables: training (X1), motivation (X2), and rewards (X3), on the dependent variable, professionalism (Y). The findings indicate that while training (X1) did not exhibit a significant direct effect, motivation (X2) demonstrated a positive and significant influence on professionalism. Moreover, rewards (X3) did not directly impact professionalism but showed a significant association with its enhancement. These results underscore the nuanced influences of training, motivation, and rewards on teacher professionalism, emphasizing the importance of tailored strategies in educational settings to foster continuous professional development among educators.